Literature Review: Utilization of Cloud Computing in Drip Irrigation System - Ida Ayu Devian Branitasandhini Putra; Jasmine Nabila Ayoedya; Heri Wijayanto (Infact: International Journal of Computers, 2026)
Low levels of food production can be caused by some countries still using traditional farming methods, which can affect crop yields. Farmers who still use conventional farming methods often cause inefficient use of resources. This can be overcome by using smart farming methods by utilize technology. This technology is known as the Internet of Things. IoT technology in agriculture is utilized in irrigation systems to create smart irrigation systems. In addition to utilizing IoT in the use of smart irrigation systems in agriculture, irrigation systems also utilize Cloud Computing. The purpose of this literature review is to examine the use of Cloud Computing in IoT-based smart irrigation systems, as well as to identify the benefits and challenges associated with efficient water use and agricultural consumption. This study uses a narrative literature review method by collecting literature studies related to the use of IoT and Cloud Computing in drip irrigation systems. From the results of the analysis of five journals discussing the use of Cloud Computing in IoT-based smart irrigation systems, it can be concluded that the use of Cloud Computing technology in smart irrigation systems provides various significant benefits, especially in terms of water use efficiency and better irrigation management.